Pengaruh Belajar Bahasa Arab terhadap Kemampuan Maharotul Istima’(Mendengar) - Hilmani, Muhammad Fauzan; Winanto; Syauqi, Sidqi Adam; Hidayat, Wahyu; Indriana, Dina (JOURNAL SAINS STUDENT RESEARCH, 2025)
Arabic plays an important role in an increasingly connected world, not only in religious aspects, but also in business, politics and education. Recognized as an international language by the United Nations since 1973, it is attracting increasing attention for learning. The aim of learning Arabic is to improve communication skills, both active and passive. The main point in the learning process is the listening skill, which is the foundation for mastering other skills such as speaking, reading, and writing. This study applied a quantitative approach and collected data through questionnaires that were statistically analyzed. The findings of this study underline the importance of creative teaching methods, such as language games, to create a fun and effective learning environment, especially for beginners. The relationship between teachers and students is also considered an important element in successful learning.